Polyurea Dendrimer Folate-Targeted Nanodelivery of l-Buthionine Sulfoximine as a Tool to Tackle Ovarian Cancer Chemoresistance - Adriana Cruz; Pedro Mota; Cristiano Ramos; Rita F. Pires; Cindy Mendes; José P. Silva; Sofia C. Nunes; Vasco D. B. Bonifácio; Jacinta Serpa (MDPI AG, 2020)
Ovarian cancer is a highly lethal disease, mainly due to chemoresistance. Our previous studies on metabolic remodeling in ovarian cancer have supported that the reliance on glutathione (GSH) bioavailability is a main adaptive metabolic mechanism, also accounting for chemoresistance to conventional therapy based on platinum salts. In this study, we tested the effects of the in vitro inhibition of GSH synthesis on the restoration of ovarian cancer cells sensitivity to carboplatin. GSH synthesis was inhibited by exposing cells to l-buthionine sulfoximine (l-BSO), an inhibitor of γ-glutamylcysteine ligase (GCL). Given the systemic toxicity of l-BSO, we developed a new formulation using polyurea (PURE) dendrimers nanoparticles (l-BSO@PUREG4-FA2), targeting l-BSO delivery in a folate functionalized nanoparticle.